Validasi Metode Analisis Formalin dan Aplikasinya Pada Ikan Asin - Suseno, Dedy (JURNAL AGROINDUSTRI HALAL, 2021)
As a Muslim, it must obligatory to consume halal and thayyib food. This is already ALLAH Subhanahu Wa Ta’ala commanded in the Alquran at surah al-maidah verse 168. Salted fish is one of the familiar foods for Indonesian people. Until now formaldehyde is still widely used to preserve salted fish, whereas its use as a food supplement is prohibited. Methods validation is intended to ensure that methods used for formaldehyde analysis in this research are appropriate so that it will produce correct and accurate data. This research aims to validate two methods are chromatropic acid and Nash for formaldehyde analysis and analyze the content of formalin in salted fish. The result shows that R2, LOD, LOQ, and the largest recovery value in chromatropic acid are 0.9985, 0.0926 ppm, 0.3088 ppm, dan 54.21%. The result of method validation on Nash shows that R2, LOD, LOQ, and the largest recovery value are 0.9999, 0.0247 ppm, 0.0822 ppm dan 42.72%. The biggest formaldehyde concentration in salted fish sold at market A and B are 0.4671 ppm dan 0.815 ppm.